2018
DOI: 10.26434/chemrxiv.7464776.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CuH-Catalyzed Enantioselective Ketone Allylation with 1,3-Dienes: Scope, Mechanism, and Applications

Abstract: <p>Chiral tertiary alcohols are important building blocks for the synthesis of pharmaceutical agents and biologically active natural products. The addition of carbon nucleophiles to ketones is the most common approach to tertiary alcohol synthesis, but traditionally relies on stoichiometric organometallic reagents that are difficult to prepare, sensitive, and uneconomical. We describe a mild and efficient method for the copper-catalyzed allylation of ketones, using widely available 1,3-dienes as allylmet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 8 publications
3
19
0
Order By: Relevance
“…1 The DFT calculations were carried out at a level of theory similar to that in our recent computational study on the CuH-catalyzed allylation of ketone and 1,3-dienes. 2 A benchmark study in our previous publication indicated the predicted enantio-and diastereoselectivities using this level of theory are consistent with those from a few other popular modern density functionals and solvation models. 2 Here, geometry optimizations were performed in the gas phase with the B3LYP functional and a mixed basis set of SDD for Cu and 6-31G(d) for other atoms.…”
Section: Computational Detailssupporting
confidence: 66%
See 2 more Smart Citations
“…1 The DFT calculations were carried out at a level of theory similar to that in our recent computational study on the CuH-catalyzed allylation of ketone and 1,3-dienes. 2 A benchmark study in our previous publication indicated the predicted enantio-and diastereoselectivities using this level of theory are consistent with those from a few other popular modern density functionals and solvation models. 2 Here, geometry optimizations were performed in the gas phase with the B3LYP functional and a mixed basis set of SDD for Cu and 6-31G(d) for other atoms.…”
Section: Computational Detailssupporting
confidence: 66%
“…2 A benchmark study in our previous publication indicated the predicted enantio-and diastereoselectivities using this level of theory are consistent with those from a few other popular modern density functionals and solvation models. 2 Here, geometry optimizations were performed in the gas phase with the B3LYP functional and a mixed basis set of SDD for Cu and 6-31G(d) for other atoms. Single point energies were calculated with the M06 functional 3,4 and a mixed basis set of SDD for Cu and 6-311+G(d,p) for other atoms.…”
Section: Computational Detailssupporting
confidence: 66%
See 1 more Smart Citation
“…The enantioselective coupling of two prochiral molecules constitutes an effective strategy for the construction of multiple vicinal stereogenic centers in a single operation. [1][2][3][4][5][6][7][8][9][10][11][12] In particular, the reaction between prochiral vinyl heterocycles and ketones provides rapid entry to enantiomerically enriched tertiary alcohols, which are prominent substructures in pharmaceuticals and natural products (Figure 1A). [12][13][14] Prototypical approaches to form enantioenriched tertiary alcohols have relied on utilizing stoichiometric chiral auxiliaries to relay stereochemical information to the product.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, metal-hydride mediated hydroarylation of dienes has been developed rapidly, either through C-H bond activation of arenes [21][22][23][24] or by adding additional hydride reagents when aryl boronic acids 25,26 or aryl halides were used. 27,28 In comparison, hydroalkylation of dienes remains less explored. As early as 1970s, Hata and coworkers reported the first palladium-catalyzed addition of 1,3-dicarbonyl compounds to dienes, although the products contain mixtures of both 1,2-and 1,4-additions (Fig.…”
mentioning
confidence: 99%